A SOLITARY QUASISUBJECT IN THE EPOCH OF POSTMODERNITY: CRITICS OF THE GLOBILIZED SOCIETY - Ігнатенко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The philosophic and anthropologic research inquires into the specificity of manifestation of a solitude phenomenon in the epoch of postmodernity in context of an analyses of the virtual communication situation.